Eye Tracking Reveals Physical Therapist Decision Making While Evaluating Standing Balance Performance - Emma Nigrelli; Wendy Carender; Kathleen H. Sienko; Leia Stirling (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2025)
Physical therapists (PTs) play an important role in balance rehabilitation as they make observations of patients to aid their decision making. Eye tracking can provide a record of these observations. Prior work has used eye tracking to compare PTs’ visual behaviors across different experience levels; however, these studies have not considered how PTs’ visual behaviors change with respect to patients’ performances. This study aimed to identify the regions of the body PT participants focused on while evaluating standing balance and whether these regions of interest change with different observed levels of balance performance. Eleven pairs of older adults and PTs participated. The PT participants wore eye tracking glasses while watching the older adult participants perform standing balance exercises and provided performance ratings. Areas of interest, including the head, torso, upper extremities (UE), and lower extremities (LE), were defined to quantify the number and average duration of visits. PTs had the most and longest visits to the LE and the fewest and shortest visits to the UE across all ratings. As balance performance worsened, PTs increased the number of visits to the head, while decreasing the average visit duration to the torso and LE. These results suggest lower body balance strategies are important visual characteristics PTs consider while evaluating balance performance and, as exercises become more challenging, PTs demonstrate increasingly rapid visual scans of the whole-body to continually update their understanding of performance. This understanding of PT visual behaviors has implications for the future development of PT-informed balance assessment models.